Pengembangan Buku Keterampilan Menulis Intensif Kebahasaan Berbasis Problem Based Learning dan Artifcial Intelligence di Perguruan Tinggi - Puspita, Nidde; Susmita, Nelvia (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
Quality writing skills include not only technical skills, but also higher order thinking skills (HOTS), such as analysis, evaluation, and creation. This research aims to develop a Problem-Based Learning (PBL) and Artificial Intelligence (AI)-based intensive writing skills book for university students. The importance of teaching materials that not only support the mastery of writing skills, but also improve higher order thinking skills (HOTS). The research method used is Research and Development (R&D) with the Four-D model (Define, Design, Develop, and Disseminate). The development process includes needs analysis, design, validation, practicality test, and effectiveness test of textbooks. The results showed that the developed textbook was able to motivate students in learning to write and improve their critical thinking skills. The book is also supported by AI technology that provides automatic and relevant feedback for students. In conclusion, the integration of PBL and AI in this intensive writing skill book is effective in improving the quality of students' writing learning in higher education.